KNOWLEDGE, ATTIUDES AND PRACTICES TOWARDS FOOD AND DRUG EXPIRY DATE AMONG INHABITANTS OF IAD HUSSEIN AREA, AL NASER LOCALITY, KHARTOUM STATE, 2012 - Ahmmed, Hatim Rahamt Alla Mohammed; Mohammed, Somiya Gutbi Salim (European Scientific Journal, ESJ, 2014)
Food safety involves the safe handling of food from the time it is grown, packaged, distributed, and prepared to prevent foodborne illnesses. Foodborne illness may be caused by bacteria that grow on food or by viruses that are spread because food is not cleaned, stored, or handled properly. Expiry dates are indicative of the safety and nutritional quality of foodstuffs and nutrition. The risk of food-borne diseases increases after the expiration date, especially if the storage conditions are less than optimal. A descriptive cross-sectional study was conducted in Iad Hussein, which lies to the south of Khartoum, with the aim to evaluate the consumer KAP to food and drug expiry date. Four hundred households were selected as a sample. Interviews, questionnaires, focus group discussion and observations were used for collecting data. These data were analyzed and tested by the SPSS and significant tests. Results showed that 69% of the participants do not check the expiry date labels at all;there was a strong association between participants’ income and knowledge on one hand and checking expiry date labels on the other, more than half of the participants cared about the proper storage conditions of food and drugs. On the basis of the findings a set recommendations was formulated as; health education intervention is needed for promoting proper storage conditions of food and drugs and practices concerning checking the food or drug expiry date labels and to establish societies to deal with food and drug safety.